POLA KOMUNIKASI KEAGAMAAN DALAM MEMBENTUK KEPRIBADIAN ANAK - Imam Subqi (INJECT (Interdisciplinary Journal of Communication), 2016)
This article specifically discusses the pattern of Islamic construction which is expected to make up the individual identity and marks them as Muslim, both are shown in their behavior. Behavior looks like walking, eating, drinking, communicating with teachers, parents, friends and others. While the inner behavior proposed by Frank Burton Cheyne is sincere, don't envy and other commendable attitudes rising from their inner feeling. From variety of thoughts above, the construction of the Islamic religion, addressed to children will be able to provide a steady view oflife based on the values of Islam, and they were also able to get used to think, behave according to the norms of Islam or personality in accordance with the teachings of Islam although they have a different default factors.Abstrak Artikel ini secara spesifik membahas tentang pola keberagamaan Islam yang diharapkan mampu membenahi kepribadian individu dan menandai mereka sebagai Muslim, dua hal tersebut nampak dalam tingkah laku mereka. Tingkah laku seperti berjalan, makan, minum, hubungan dengan guru, orang tua, teman-teman, dan yang lainya. Sedangkan menurut Frank Burton Cheyne memaknai tingkah laku batiniah sebagai keiklasan, tidak iri, dan sikap terpuji lain yang muncul dari dalam perasaan mereka. Dari berbagai pendapat diatas, pengajaran agama islam yang diberikan kepada anak-anak mampu memberikan pandangan hidup yang kuat berdasarkan nilai keislaman dan mereka mampu terbiasa berfikir, dan bertindak berdasarkan norma keislaman atau pribadi berdasarkan ajaran islam meskipun mereka mempunyai faktor kesulitan yang berbeda.